A Comparative Study of the Optimal Sizing and Management of Off-Grid Solar/Wind/Diesel and Battery Energy Systems for Remote Areas - Thirunavukkarasu, M.; Sawle, Yashwant (Frontiers in Energy Research, 2021)
Electrification in rural areas is relatively costly compared to urban areas. So, the aim of this research is to identify the best combination of hybrid renewable energy systems (HRES) to satisfy the load demand in a sustainable and cost-efficient way. The techno-economic study of standalone hybrid Photovoltaic-wind turbine-diesel-battery-converter energy systems based on the hybrid optimization model for electric renewable (HOMER) simulation has been analyzed for various locations in Tamil Nadu state, India. Various combinations of the systems have been compared and analyzed based on the performance of their technical parameters, costs, the electrical power production of each source, and unmet load. The findings indicated that the off-grid solar-wind-diesel-battery configuration is the most economical for all the sites among other system configurations. Comparing with conventional diesel generators among all the locations, a combination of solar/wind/diesel/battery is the economically best design for Thoothukudi, with the least and most reliable solution in terms of net present cost and cost of energy. Also, the impact of intermittent variables becomes significant, so sensitivity analysis for the various parameters has been carried out. Moreover, the results of the proposed study imply that the proposed renewable energy system in remote sites could be a more economical measure.